Is Valgus Cut Angle Based on Radiographic Measurements in Total Knee Arthroplasty Really Inaccurate? A Comparison of Two- and Three-Dimensional Measurements - Liu, LiMing; Lei, Kai; Chen, Xin; Fan, HuaQuan; Yang, Liu; Guo, Lin (The Journal of Knee Surgery, 2021)
Radiographs are widely used to measure distal femoral valgus cut angle (VCA) in total knee arthroplasty (TKA), but its accuracy is controversial. This study used three-dimensional (3D) reconstruction models to verify the accuracy of VCA measurements on radiographs, and explore the correlation of VCA with hip–knee–ankle (HKA) angle and lateral femoral bowing angle (FBA). A total of 444 osteoarthritis knees of 444 patients from August 2016 to June 2018 was included retrospectively. On radiographs, two-dimensional VCA (VCA-2D) was measured between the femoral mechanical axis and the distal femoral anatomical axis, and HKA was measured between the femoral mechanical axis and the tibial mechanical axis. On the coronal projection of computed tomography 3D models, the anatomical landmarks used for VCA-3D measurements were the same as those on the radiographs, FBA was measured between the proximal and distal femoral anatomical axis. The distributions of VCA-2D and VCA-3D were evaluated by means and variances. The correlation between HKA and VCA and between FBA and VCA was explored. There was a statistical difference between VCA-2D and VCA-3D (p < 0.001), but the deviation was very small (0.15 ± 0.69 degrees), 83.3% of the deviations were less than 1 degree. VCA would increase both in 2D and 3D with increasing of FBA and HKA varus. There was no statistically significant difference between VCA-2D and VCA-3D in patients with moderate varus knees (0–8 degrees of varus) and mild bowing femurs (FBA <5 degrees). Overall, the deviation caused by using radiography to measure VCA was negligible. VCA measurements using radiographs were accurate in patients with moderate varus knees and mildly bowed femurs. This study reflects level of evidence III.
Keywords: total knee arthroplasty; valgus cut angle; radiograph; three-dimensional; computed tomography